Multipoint Left Ventricular Pacing in a Single Coronary Sinus Branch Improves Mid‐Term Echocardiographic and Clinical Response to Cardiac Resynchronization Therapy. (19th September 2014) - PAPPONE, CARLO; ĆALOVIĆ, ŽARKO; VICEDOMINI, GABRIELE; CUKO, AMARILD; MCSPADDEN, LUKE C.; RYU, KYUNGMOO; ROMANO, ENRICO; BALDI, MARIO; SAVIANO, MASSIMO; PAPPONE, ALESSIA; CIACCIO, CRISTIANO; GIANNELLI, LUIGI; et al.
Multipoint LV Pacing Improves Mid‐Term CRT Response Introduction Cardiac resynchronization therapy (CRT) with multipoint left ventricular (LV) pacing in a single coronary sinus branch improves acute LV function. We hypothesized that multipoint pacing (MPP) can improve midterm echocardiographic and clinical response compared with conventional CRT. Methods and Results Consecutive patients receiving a CRT implant (Unify Quadra MP™ or Quadra Assura MP™ CRT‐D and Quartet™ LV lead, St. Jude Medical, Sylmar, CA, USA) were randomized to receive biventricular (BiV) pacing with either conventional LV pacing (CONV group) or MPP (MPP group). For each patient, an optimal pacing configuration for the assigned pacing mode was programmed based on intraoperative pressure‐volume (PV) loop measurements. A clinical evaluation and transthoracic echocardiogram were performed before implant (BASELINE) and at 3 months postimplant and analyzed by a blinded observer. A reduction in end‐systolic volume (ESV) of ≥15% relative to BASELINE was prospectively defined as response to CRT. Forty‐four patients (NYHA Class III, EF 29 ± 6%, QRS duration 152 ± 17 milliseconds) were enrolled and randomized. One patient in the MPP group was lost to follow‐up and excluded from further analysis. After 3 months, 11 of 22 (50%) CONV patients and 16 of 21 (76%) MPP patients were classified as responders. ESV reduction, EF increase, and NYHA class reduction relative to BASELINE were significantly greater in the MPP group than in the CONV group (ESV: −21.0 ± 13.9 vs. −12.6 ± 11.1%, P = 0.03; EF: +9.8 ± 5.1 vs. +2.0 ± 7.8 percentage points, P < 0.001; ΔNYHA: −1.05 ± 0.22 vs. −0.72 ± 0.46 functional classes, P = 0.006). Conclusion PV loop optimized BiV pacing with MPP resulted in an improved rate of response to CRT.